2017
DOI: 10.1111/ppa.12688
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and inoculum density‐dependent interactions between clubroot resistant canola (Brassica napus) and Plasmodiophora brassicae

Abstract: To mitigate the impact and dissemination of clubroot in western Canada, canola (Brassica napus) producers have relied on clubroot resistance traits. However, in 2013 and 2014, new strains of the clubroot pathogen, Plasmodiophora brassicae, emerged that are virulent on most clubroot‐resistant (CR) canola genotypes. Novel strains of the pathogen were inoculated onto two susceptible canola cultivars, one resistant line and six CR cultivars. Although all cultivars/lines showed a susceptible response to inoculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…On the other hand, low levels of high virulent isolates have existed within the population of P. brassicae for some years, and the population of high virulent isolates increased because of the selection pressure exerted by extensive use of clubroot-resistant cultivars. Our results confirm previous work [ 33 ] showing that the severity of disease reaction, root hair infection rates, and the amount of P. brassicae DNA present in each canola genotype varied depending on the strain of the pathogen. Similarly, an earlier study demonstrated strong positive correlations between the amount of P. brassicae DNA and the level of root hair infection, where this relationship was stronger for the resistant cultivar than for the susceptible one [ 9 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…On the other hand, low levels of high virulent isolates have existed within the population of P. brassicae for some years, and the population of high virulent isolates increased because of the selection pressure exerted by extensive use of clubroot-resistant cultivars. Our results confirm previous work [ 33 ] showing that the severity of disease reaction, root hair infection rates, and the amount of P. brassicae DNA present in each canola genotype varied depending on the strain of the pathogen. Similarly, an earlier study demonstrated strong positive correlations between the amount of P. brassicae DNA and the level of root hair infection, where this relationship was stronger for the resistant cultivar than for the susceptible one [ 9 ].…”
Section: Discussionsupporting
confidence: 91%
“…Mendel, often found not to be durable for a long time, and the overcoming of resistance after a few growing seasons in clubroot-infested fields have been reported in different countries [1,2,18,19,24]. Generally, it was found that increasing inoculum amounts translate into increasing values of both disease incidence and severity [26,33]. However, the influence of the pathotype virulence and the susceptibility of the host cultivar on this relationship has not been intensively investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Common diseases in rapeseed reported worldwide includes blackleg disease, caused by Leptosphaeria maculans [ 110 , 111 ] clubroot, caused by Plasmodiopora brassicae [ 112 , 113 ] and Sclerotinia stem rot, caused by Sclerotinia sclerotiorum [ 114 , 115 ]. The availability of genomic data and genetic maps of Brassica species, along with associated bioinformatics tools, allow deeper dissection of the genetic architecture of resistance.…”
Section: Breeding For Economically Important Agronomic Traits Of mentioning
confidence: 99%